The Playbook of Russian Military Actions: Eurasianism and National Messianism - Gilbert Ahamer (Cadmus)
How is it ever possible to experience such a cruel war in Europe? Why has Ukraine been attacked by Russia? What are the credible details? Why did international institutions fail to prevent tensions from becoming cruel? What are the sociocultural roots and the underlying paradigms of this conflict? To what extent was it planned? Based on over a hundred concrete press references, this article answers these questions as much as possible and suggests a way out in a brief concluding fourth section. Apart from encouraging individual responsibility (single soldiers or commanders) and national responsibility (generating paradigms and narratives of collective identities), it is useful to perceive a level of planetary responsibility that cares for effective in-time rescue in derailed disastrous situations, namely when institutions and procedures fail to keep peace. UN bodies and OSCE exist but have not been fully effective. The article thus calls for effective functioning of systems at the individual, national and global levels.